Marine fisheries and biodiversity management in Maharashtra: Status, challenges and opportunities - LAKRA, W S; S, RAMKUMAR; GOPALAKRISHNAN, A (The Indian Journal of Animal Sciences, 2021)
Fisheries plays a pivotal role in the economy, food security, foreign exchange earnings and employment of the coastal population. Maharashtra is bestowed with a coastline of 720 km spread over 7 coastal districts, viz. Thane, Palghar, Mumbai city, Mumbai suburban, Raigad, Ratnagiri and Sindhudurg along the Arabian sea with rich marine fishery resources. There are 25 fishing zones in the seven districts with 173 fish landing centres. The total marine fish production from the state during 2018-19 was 4.6 MT valued at `6298 crores (DOF, Government of Maharashtra). The state offers huge potential for the sustainable utilization of the marine bioresources for fisheries, mariculture, coastal aquaculture and post -harvest development and exports. Maharashtra falls under the North- West coast which contributes the highest (32.8%) in the total catch during 2019-20. The major share is contributed by pelagic resources (39%), followed by crustaceans (31%), demersal comprising 22% and molluscs (7%). The prominent species/groupwise landings include non-penaeid shrimp (21%), penaeid shrimp (9%), Bombay duck and croakers (8.2%), Indian mackeral (6.9%), threadfin breams (5.9%), squids (5.1%), ribbon fishes (4.1%), golden anchovy (4%), horse mackerel (3.5%), cuttle fish (2.1%), silver pomfret (2.0%). The trawl fishing accounted for 55%, set bagnet (SBN/Dolnet) 23%, purse seines (15%) and gillnet (7%) (CMFRI Annual Report 2019).